2022
DOI: 10.1111/jipb.13350
|View full text |Cite
|
Sign up to set email alerts
|

COP1 SUPPRESSOR 6 represses the PIF4 and PIF5 action to promote light‐inhibited hypocotyl growth

Abstract: Light signaling precisely controls photomorphogenic development in plants. PHYTOCHROME INTERACTING FACTOR 4 and 5 (PIF4 and PIF5) play critical roles in the regulation of this developmental process. In this study, we report CONSTITUTIVELY PHOTOMORPHOGENIC 1 SUPPRESSOR 6 (CSU6) functions as a key regulator of light signaling. Loss of CSU6 function largely rescues the cop1‐6 constitutively photomorphogenic phenotype. CSU6 promotes hypocotyl growth in the dark, but inhibits hypocotyl elongation in the light. CSU6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…To better understand the basis of COP1 function, we performed a genetic screen to identify the suppressors of cop1-6 in the dark. In addition to the published recessive cop1-6 suppressor mutants [42][43][44][45][46][47] , we identified and isolated 13 additional extragenic dominant suppressors of cop1-6 (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the basis of COP1 function, we performed a genetic screen to identify the suppressors of cop1-6 in the dark. In addition to the published recessive cop1-6 suppressor mutants [42][43][44][45][46][47] , we identified and isolated 13 additional extragenic dominant suppressors of cop1-6 (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the cop1-6 recessive suppressers csu1 to csu6 have distinct functions [42][43][44][45][46][47] . Given our data suggesting that all six of the DCS proteins are components of the spliceosome, we considered COP1's potential function in mRNA splicing.…”
Section: Light and Cop1 Control Genome-wide Alternative Splicing In A...mentioning
confidence: 99%
“…The PIF4-ABI4 complex synergistically promotes primary seed dormancy Transcription factor PIF4 was initially characterized as a key component of phytochrome-and auxin-signaling pathways (Lau and Deng, 2010;Zhao and Bao, 2021), which served in several biological processes, including young seedling hypocotyl elongation (Gao et al, 2022;Lan et al, 2022), plant thermomorphogenesis, heat response and leaf senescence (Li et al, 2021;Lee et al, 2021b), as well as in response to several phytohormones and diverse environmental cues (Choi and Oh, 2016;Huang et al, 2019;Yan et al, 2020b;Qiu et al, 2021;Xu and Zhu, 2021;.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation and interaction of one TF by another is an efficient and effective mechanism to respond to environmental stimuli. For example, Arabidopsis CONSTITUTIVELY PHOTOMORPHOGENIC 1 SUPPRESSOR 6 (CSU6) represses hypocotyl growth via transcriptional and biochemical regulation of PHYTOCHROME‐INTERACTING FACTOR 4 (PIF4) and PIF5 (Lan et al, 2022). By contrast, one recent study showed that a bHLH TF, bHLH38, dually regulates OsDREB2A at the transcriptional level and via direct protein–protein interaction to promote stress tolerance (Du et al, 2023).…”
Section: Discussionmentioning
confidence: 99%